The elaboration of teaching experience in the early years of Elementary School - Toscano, Carlos (2013)
In this work it is presented and discussed part of the outcomes from a research, which took place between 2006 and 2009 with newly-graduated Pedagogy students who have been teachers in the first years of primary school. This study took the theoretical and methodological contributions from Bakhtin, Lahire and Chartier as reference, taking into consideration the fact that these authors, within their specificity, place in the social practices the genesis of the specifically human, highlighting in this process the role of the other and of the semiotic mediation. The data shared here refers to one participant of this research, who at that time was the main class teacher in a third grade of the Elementary and public schoo in Paraná; it talks about this professional experience. The study while of the account of the teacher’s professional experience contributed to the enlargement of the visibility of the conditions in which real subjects have become teachers of the first years of primary school, and ended up highlighting a singular entwinement with various social voices which meet, confront each other and are situated in different time and space: some of them belong to the beginning of their initial formation, mediated by formative professors, others belong to their immediate interlocutors (colleagues/pedagogical team) and there are also voices found in the local administration, which, in turn, mediate the educational policy signaling broader determinations which mark an specific historical epoch.